2017
DOI: 10.3892/ol.2017.5911
|View full text |Cite
|
Sign up to set email alerts
|

The context of prostate cancer genomics in personalized medicine

Abstract: Abstract. Prostate cancer is one of the most common types of cancer in males. Heterogeneous genomic aberrations may lead to prostate cancer onset, progression and metastasis. This heterogeneity also contributes to the variety in cancer risk and outcomes, different drug responses and progression, observed between individual patients. Classical prognostic factors, including prostate-specific antigen, Gleason Score and clinical tumor staging, are not sufficient to portray the complexity of a clinically relevant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 76 publications
(110 reference statements)
0
12
0
Order By: Relevance
“…Counts for CTCs in PB and MTCs in BMA were 0 cells ml −1 and 3673 cells ml −1 , respectively (figure 4(a)). The HD-SCA threshold for a positive sample is ⩾1 cell per case based on previous studies, making BMA positive for this patient [23,24]. MTCs were detected as both single cells and clusters of 2-5 cells (25%), 6-10 cells (3%), and 11 + cells (1%) (figure 4(a)).…”
Section: Single Cell Morphometric Analysis Of Identified Tumor Cellsmentioning
confidence: 86%
“…Counts for CTCs in PB and MTCs in BMA were 0 cells ml −1 and 3673 cells ml −1 , respectively (figure 4(a)). The HD-SCA threshold for a positive sample is ⩾1 cell per case based on previous studies, making BMA positive for this patient [23,24]. MTCs were detected as both single cells and clusters of 2-5 cells (25%), 6-10 cells (3%), and 11 + cells (1%) (figure 4(a)).…”
Section: Single Cell Morphometric Analysis Of Identified Tumor Cellsmentioning
confidence: 86%
“…So far, prostate-specific antigen (PSA) has been mostly used for early detection and recurrence evaluation as a biomarker. Gleason score is a classical prognostic factor but not sufficient to portray the complexity of clinical prognosis 2. The heterogeneous genomic property of PCa can lead to the difficulty in survival prognosis and therapy monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Gleason score is a classical prognostic factor but not sufficient to portray the complexity of clinical prognosis. 2 The heterogeneous genomic property of PCa can lead to the difficulty in survival prognosis and therapy monitoring. Therefore, there is an urgent need for novel effective parameters to predict outcomes for treatment decision.…”
Section: Introductionmentioning
confidence: 99%
“…PCa is one of the most common malignant tumors in the male reproductive and urinary system. 26 A recent study demonstrated that lncRNAs are also involved in the occurrence of PCa, and Zhu et al 27 found that lncRNA H19 inhibits the metastasis of PCa through targeting miR-675 and TGFBI. Moreover, Shi et al suggested that lncRNA APP promotes PCa development through competitively binding to miR-218.…”
Section: Discussionmentioning
confidence: 99%